Bakteri Endofit dari Tumbuhan Paku-pakuan sebagai Agens Hayati Rhizoctonia solani dan Pemacu Pertumbuhan Tanaman Padi - Asmoro, Prayogo Probo; munif, abdul (Jurnal Fitopatologi Indonesia, 2020)
Rhizoctonia solani is one of the important pathogens that causes sheath blight disease in rice plants that are difficult to be controlled. Biological control with endophytic bacteria is a potential alternative because of its ability to live in plant tissues without causing symptoms of disease and can increase plant growth and resistance. The purpose of this study was to explore endophytic bacteria from root and stem parts from three different types of ferns, namely Salvinia molesta (water nail), Pteris ensiformis (terrestrial nail), and Drymoglossum pilosolloides (epiphytic nails) and to evaluate their potential as biological control agents against R. solani and plant growth promoters. Isolation of endophytic bacteria was grown on trypsic soy agar (TSA) and nutrient agar (NA). Bacterial isolates were purified and tested for their biosafety by hypersensitivity and hemolysis test. A total of 178 isolates of endophytic bacteria were isolated and 88 isolates showed negative reactions after hypersensitivity and hemolysis test. The isolates were tested for their antagonism activity under in vitro test against R. solani and plant growth activity. The result showed four isolates of endophytic bacteria, namely APE15, APE22, APE33, and APE35 with inhibition activity of 27% -76% in three different medium TSA, potato dextrose agar (PDA) and TSA + PDA medium. Endophytic bacteria are also able to increase rice germination up to 4.9%–48.8% and increase rice root display of 68.3% –95.4%, shoot length 53.2%–87.3%, plant fresh weight 49.07%–90.65% and plant dry weight 48.1%–87.3%. These results indicated that ferns contain several endophytic bacteria that can be cultured which have effective antimicrobial compounds, and can be used as biological control agent against R. solani and plant growth promoters.